Formulation and in-vitro evaluation of Chitosan films containing tetracycline for the treatment of periodontitis - Ahmed, Mohammed Gulzar; Charyulu, R Narayana; Harish, N M; Prabhu, Prabhakar (Asian Journal of Pharmaceutics (AJP), 2014)
Tetracycline is a broad spectrum antimicrobial agent, which is formulated into films and evaluated for the treatment of periodontitis. Chitosan films containing tetracycline in three different concentrations (10, 20, and 30% w/w to the weight of polymer) were prepared by the solution casting method, using 1% v/v acetic acid solution. The prepared films were evaluated for various properties such as weight variation, tensile strength, stability studies, in-vitro release, and mass balance studies. Further films were cross-linked in order to extend the drug release. Average weight and thickness among the different films was uniform.Tensile strength was maximum for plain films and minimum for films containing the highest percentage of the drug or cross-linked films. The stability studies did not show any significant changes. Static dissolution studies showed a burst release initially followed by a progressive fall in the release of the drug, and also showed extended release when cross-linking was attempted. The in-vitro release kinetics of tetracycline followed the zero order pattern. The fact that the mass balance studies done after in-vitro dissolution did not deviate by more than 3% from the experimental drug content, confirms that the drug is in free form rather than bound to the polymer.